I am struggling with the following question.

Let $\{a_n\}_{n=1}^{\infty}$ be a real sequence and $A_n = (-\infty, a_n](n\geq 1)$. Prove the following.

  1. $\exists \lim_{n\to \infty}A_n \Rightarrow \exists \lim_{n\to \infty}a_n \in [-\infty,\infty]$

  2. Converse of 1 does not hold.

(Hint: 1. Prove that $\liminf a_n < \limsup a_n \Rightarrow \liminf A_n \subsetneq \limsup A_n$ , 2: Counterexample is $a_n =(-1)^n/n.$

My approach to 1. was as follows.

(1)$\bigcap_{k\geq n}(-\infty, a_k] = (-\infty, \inf_{k\geq n}a_k]$

if $x\in \bigcap_{k\geq n}(-\infty, a_k]$ then $\forall k\geq n, x\leq a_k.$ This means that $x$ is a lower bound of $\{a_k\}_{k\geq n}$ . By definition of inf, $x\leq \inf_{k\geq n}a_k$ Therefore $x\in (-\infty, \inf_{k\geq n}a_k]$.

if $x\in (-\infty, \inf_{k\geq n}a_k]$ then since $\inf_{k\geq n}a_k \leq a_k (\forall k\geq n)$,$x\in (-\infty, a_k](\forall k\geq n)$. Therefore $x\in \bigcap_{k\geq n}(-\infty, a_k]$.

This means that $\bigcap_{k\geq n}(-\infty, a_n] = (-\infty, \inf_{k\geq n}a_k]$.

(2)$\bigcup_{n=1}^{\infty}(-\infty, \inf_{k\geq n}a_k] = (-\infty, \lim_{n\to \infty}\inf_{k\geq n}a_k]$

As $\{\inf_{k\geq n}a_k\}_n$ is a monotone increase sequence and bounded by each element of $\{a_n\}_n$, $\{\inf_{k\geq n}a_k\}_n$ converges to its least upper bound. Therefore $\inf_{k\geq n}a_k \leq \lim_{n\to \infty}\inf_{k\geq n}a_k (\forall n \in \mathbb{N}$).

If $x\in \bigcup_{n=1}^{\infty}(-\infty, \inf_{k\geq n}a_k]$ then $\exists n\in \mathbb{N}, x\in (-\infty, \inf_{k\geq n}a_k]$. Since $\inf_{k\geq n}a_k \leq \lim_{n\to \infty}\inf_{k\geq n}a_k (\forall n \in \mathbb{N}$), $x\in (-\infty, \lim_{n\to \infty}\inf_{k\geq n}a_k]$.

If $x\in (-\infty, \lim_{n\to \infty}\inf_{k\geq n}a_k]$, as $\lim_{n\to \infty}\inf_{k\geq n}a_k$ is the least upper bound, $\exists m\in \mathbb{N}, x\in (-\infty, \inf_{k\geq m}a_k]$. therefore $x\in \bigcup_{n=1}^{\infty}(-\infty, \inf_{k\geq n}a_k]$.

This means that$\bigcup_{n=1}^{\infty}(-\infty, \inf_{k\geq n}a_k] = (-\infty, \lim_{n\to \infty}\inf_{k\geq n}a_k]$.

From (1) and (2), $\liminf_{n\to \infty}A_n = (-\infty, \liminf_{n\to \infty}a_n]$. By using the same method, we can prove that $\limsup_{n\to \infty}A_n = (-\infty, \limsup_{n\to \infty}a_n]$. If $\liminf a_n < \limsup a_n$ then obviously $\liminf A_n \subsetneq \limsup A_n$.

I thought this was correct, but if $\liminf_{n\to \infty}A_n = (-\infty, \liminf_{n\to \infty}a_n]$ hold then the converse of 1. should hold as $\exists \lim_{n\to \infty} a_n \Leftrightarrow \liminf a_n = \limsup a_n$. So I thought the proof above has a flaw, but I couldn't find one. Also, I could not figure out how to use the hint given in 2.

Thank you for reading.


1 Answer 1


Since $\lim\limits_n A_n$ exists, we have that:

$$\liminf A_n=\limsup A_n\Leftrightarrow\bigcup_{n=1}^\infty\bigcap_{k=n}^∞A_k=\bigcap_{n=1}^\infty\bigcup_{k=n}^∞A_k.$$ Note that: $$\bigcap_{k=n}^∞A_k=\bigcap_{k=n}^∞(-\infty,a_k]=\left(-\infty,\inf\limits_{k\geq n}a_k\right],$$ as you said. However, also not that, if $b_n$ is an increasing sequence with $b_n\to b$ and $b_n<b$, then it holds that:

$$\bigcup_{n=1}^\infty(-\infty,b_n]=(-\infty,b),$$ since $b\not\in(-\infty,b_n)$ for every $n=1,2,\ldots$. So, what actually holds is that:

$$\liminf A_n=I(-\infty,\liminf a_n),$$ where by $I(a,b)$ we denote any interval with endpoints $a,b\in\overline{\mathbb{R}}$, $a<b$. Similarly,

$$\limsup A_n=I(-\infty,\limsup a_n).$$

From this, both results are almost immediate.

  1. If $\limsup A_n=\liminf A_n$ then $I(-\infty,\limsup a_n)=I(-\infty,\liminf a_n),$ so $\liminf a_n=\limsup a_n$ and, hence $a_n$ converges.
  2. For $a_n=(-1)^n/n$, we have $$\limsup A_n=\ldots=(-\infty,0]$$ and $$\liminf A_n=(-\infty,0).$$ (both are left for you to verify, since, knowing the results, it is relatively easy to prove them).

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.